IKKε and TBK1 in diffuse large B‐cell lymphoma: A possible mechanism of action of an IKKε/TBK1 inhibitor to repress NF‐κB and IL‐10 signalling. Issue 19 (28th August 2020) - Carr, Matthew; Mamand, Sami; Chapman, Kathryn L.; Perrior, Trevor; Wagner, Simon D.
Abstract: The IKK‐related kinases, IKKε and TBK1, have essential roles in innate immunity in part through modifying MYD88 signalling from the Toll‐like receptors to regulate NF‐κB signalling. We investigated the expression and function of IKKε and TBK1, in diffuse large B‐cell lymphoma (DLBCL). DLBCL cell lines and patient‐derived xenografts were used to determine their sensitivity to IKKε and TBK1 inhibitors. To understand the function of IKKε and TBK1 secreted factors were determined following administration of inhibitors. Gene expression microarrays were used to determine the transcriptional effects of inhibitors. Higher TBK1 mRNA levels associated with poorer clinical outcome but IKKε and TBK1 were expressed in both germinal centre and non‐germinal centre types of DLBCL. Survival of cell lines Ly10, Ly03 and Pfeiffer, and of some primary human lymphoma cells, was suppressed by a small molecule IKKε/TBK1 inhibitor, DMX3433. DMX3433 reduced IL‐10 production from Ly10 and repressed NF‐κB mediated transcription. Inhibition of IKKε and TBK1 warrants further investigation as a potential therapeutic route to suppress NF‐κB signalling in lymphoma.